Ferroptosis and hepatocellular carcinoma: the emerging role of lncRNAs - Chen, Haoran; Han, Zhongyu; Su, Junyan; Song, Xuanliang; Ma, Qingquan; Lin, Yumeng; Ran, Zijin; Li, Xueping; Mou, Rongkun; Wang, Yi; Li, Dongxuan (Frontiers in Immunology, 2024)
Hepatocellular carcinoma is the most common form of primary liver cancer and poses a significant challenge to the medical community because of its high mortality rate. In recent years, ferroptosis, a unique form of cell death, has garnered widespread attention.Ferroptosis, which is characterized by iron-dependent lipid peroxidation and mitochondrial alterations, is closely associated with the pathological processes of various diseases, including hepatocellular carcinoma. Long non-coding RNAs (lncRNAs), are a type of functional RNA, and play crucial regulatory roles in a variety of biological processes. In this manuscript, we review the regulatory roles of lncRNAs in the key aspects of ferroptosis, and summarize the research progress on ferroptosisrelated lncRNAs in hepatocellular carcinoma.